Come Through the Door with Me: Pondering Inventive Practice - Beleznay, Shelley (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
The purpose of this paper is to engage readers in thinking about the art of teaching and how to support inventive practice.  Readers are invited into a classroom and immersed in a day of learning with 11 and 12-year-olds.